Handbook on the History and Culture of the Black Sea Region - Bumann, Ninja (2024)
This first handbook on the Black Sea region provides an overview on relevant structural features from a cultural-historical perspective and thereby examines to what extent this region constitutes a historical meso-region sui generis. Particular attention is paid to phenomena and developments which connect the different shores of the Black Sea and present a unifying characteristic of the region.